Analysis of the Implementation of the BPJS Patient Contact Rate at the Cibodas Community Health Center, Lembang District, West Bandung Regency - Hadihtya, Riyan; Setiawati, Anggi (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
The implementation of the contact rate is one of the indicators that must be met by primary healthcare facilities, namely Community Health Centers (Puskesmas), as a requirement for Performance-Based Capitation (KBK). The contact rate is the number of contacts, either in the form of medical visits or consultations, made by patients at the Cibodas Community Health Center, specifically BPJS patients. The purpose of this study was to analyze the implementation of the BPJS patient contact rate at the Cibodas Community Health Center to determine whether it has met the target and the factors contributing to its achievement. This research method used a qualitative case study approach, distributing questionnaires to BPJS patients registered at the Cibodas Community Health Center. The subjects were BPJS patients registered at the Cibodas Community Health Center who had previously had contact with the Community Health Center. The results of this study indicate that the Cibodas Community Health Center has not yet achieved its contact rate target. The influencing factors were not the quality of the facility or the services provided by the healthcare workers.